Acne vulgarism treatment using ultra-short laser pulse generated by micro- and nano-ring resonator system. (April 2013) - Jalil, M. A.; Phelawan, J.; Aziz, M. S.; Saktioto, T.; Ong, C. T.; Yupapin, Preecha P.
Abstract Acne vulgaris is adebilitating dermatologic disease, and is conventionally treated by laser therapy using a microring resonator system. An evolving understanding of laser-tissue interactions involving Propioni bacterium acneproducing porphyrins, and the development of lasers to target the sebaceous glands, has led to the development of an escalating number of laser light for acne treatment. The results show that the full width at half maximum of the proposed laser pulse of 0.15 nm can be generated using a microring resonator system. The power of the laser is 200 W and the wavelength laser is 1, 032 nm, which is proposed as a treatment of acne vulgaris diseases.